2001
DOI: 10.1375/bech.18.2.92
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Depressive Symptoms in Children: The Immediate and Long-term Outcomes of a School-based Program

Abstract: The ability of a school-based program with training in both cognitive and social skills to prevent depressive symptoms in children (the Penn Prevention Program) was evaluated. Research conducted in Australia has failed to replicate the success of the program in the United States. Also evaluated was the ability of the program to reduce the symptoms of anxiety, the assumption that changes in social skills and cognitive style would be associated with changes in symptoms of depression and anxiety, and the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Three studies by other research groups in Australia have attempted to replicate PRP's effects. One study produced significant results (Quayle et al, 2001), but the other studies failed to replicate PRP's effect on depressive symptoms despite group leaders' receiving extensive PRP training (Pattison & Lynd-Stevenson, 2001;Roberts et al, 2003). A similar drop-off in effectiveness was recently reported for the Resourceful Adolescent Program (RAP).…”
Section: Comparison To Previous Studies Of Prpmentioning
confidence: 72%
See 1 more Smart Citation
“…Three studies by other research groups in Australia have attempted to replicate PRP's effects. One study produced significant results (Quayle et al, 2001), but the other studies failed to replicate PRP's effect on depressive symptoms despite group leaders' receiving extensive PRP training (Pattison & Lynd-Stevenson, 2001;Roberts et al, 2003). A similar drop-off in effectiveness was recently reported for the Resourceful Adolescent Program (RAP).…”
Section: Comparison To Previous Studies Of Prpmentioning
confidence: 72%
“…PRP's effectiveness is less clear when delivered by non-Penn therapists at sites distant from its Philadelphia base. Two recent studies of PRP conducted by research teams in Australia failed to replicate PRP's effects on depressive symptoms (Pattison & Lynd-Stevenson, 2001;Roberts, Kane, Thomson, Bishop, & Hart, 2003). The major goal of the present study was to evaluate the effectiveness and transportability (Schoenwald & Hoagwood, 2001) of PRP by examining its effects when delivered by non-PRP clinicians in a medical primary care setting.…”
mentioning
confidence: 97%
“…Only a few studies have compared prevention programs with attention control groups or alternate interventions. Pattison and Lynd-Stevenson (2001) found that PRP did not significantly reduce or prevent depressive symptoms relative to both nointervention and attention control groups. The small sample size (N = 63) may have limited power to detect effects, however.…”
Section: Introductionmentioning
confidence: 76%
“…Effect sizes were moderate to large (d > 0.60) 12-24 months postintervention (Gillham et al, 1995). However, other studies failed to replicate these findings (e.g., Pattison & Lynd-Stevenson, 2001;Roberts, Kane, Bishop, & Matthews, 2004). A review of PRP research suggests that PRP's effects are strongest when group leaders are the intervention developers, members of their research team, and graduate students who receive extensive training and supervision from the intervention developers.…”
Section: Prp's Inconsistent Effectsmentioning
confidence: 99%
“…20.5.3) by Jaycox et al (1994) as a universal inter vention with differing levels of success (e.g., Cun ningham, Brandon, and Frydenberg 1999; Pattison and Lynd-Stevenson 2001;Quayle et al 2001;Shochet et al 2001). About half of these studies found significant improvements in coping skills, attributional style, and perceived control at posttest.…”
Section: Universal Preventionmentioning
confidence: 99%